Corporate Governance and Costs of Equity: Theory and Evidence - Li, Di; Li, Erica X. N. (Management Science, 2018)
We propose and test an alternative explanation for the existence of the positive governance–return relation in the 1990s and its disappearance in the 2000s: The governance–return relation is positive under good states of the economy and negative under bad states. Corporate governance mitigates investment distortions so that firms with strong governance have more valuable investment options during booms and more valuable divestiture options during busts than the ones with weak governance. Because investment options are riskier and divestiture options are less risky than assets in place, the expected returns of strongly governed firms are higher during booms but lower during busts than the weakly governed ones. Empirical evidence is consistent with our hypothesis. This paper was accepted by Neng Wang, finance.